SWOT Analysis of Green Tourism Development Strategies in Telaga Saat, Puncak, West Java - Mohamad Afendi; Dhanik Puspitasari; Dina Mayasari Soeswoyo (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study examines the implementation of green tourism at Telaga Saat using a qualitative approach, involving in-depth interviews with five key informants (management, government, academics, Perhutani, and media). The findings reveal that the main strengths of the destination are its unique ecological features and strong community involvement, while limitations in facilities and human resource capacity remain critical weaknesses. Opportunities are identified in the support of the 2025–2029 National Medium-Term Development Plan (RPJMN) and the potential for university collaboration, whereas threats include overtourism and climate change. The TOWS matrix produces four core strategies: (1) a local product-based water conservation education package (SO), (2) eco-friendly infrastructure improvements supported by CSR (WO), (3) dynamic carrying capacity management using real-time sensors (ST), and (4) a circular waste management ecosystem (WT). Strategy implementation is prioritized for 2025–2029, with key indicators including a 40% reduction in plastic waste, ASEAN Sustainable Tourism Standard certification, and the planting of 10,000 endemic trees. The study highlights that multi-stakeholder collaboration is essential for sustaining green destinations in ecologically sensitive areas.